Access to health services and its association with chronic malnutrition in children under 5 years of age from low socioeconomic levels in Peru. A population-based analysis - Gonzales Rojas, Carlos Alejandro (2021)
Introduction: Chronic malnutrition (Stunting) is one of the main problems in developing countries. On the other hand, the health of the mother and her timely access to a health service is a relevant aspect, but the relationship that the fact of being born in a non-institutional environment has on chronic malnutrition in children under 5 is not yet known. Objectives: Our analysis aims at evaluating the association between institutional delivery and chronic malnutrition in the first 5 years of life using the ENDES-2017 database in low and very low socioeconomic levels. Methods: Analytical cross-sectional observational study with data from the Demographic and Family Health Survey (ENDES). All the analyses were carried out considering the complex sample design (svy), considering that the database comes from a survey at the time of analysis. Chi square was used for bivariate analysis for categorical variables. Crude prevalence ratios (RPc) and adjusted (RPa) were obtained through the construction of generalized linear models, using the Poisson family and the log link function. A confidence level of 95% was considered, significant p <0.05. Results: A total of 11,734 records were analyzed. The prevalence of chronic malnutrition in children under 5 years of age was 20.50% and the prevalence of non-institutional delivery was 15.53%. 92.47% of the children who received their complete vaccinations up to one year of life had institutional delivery in urban areas, while only 85.71% in rural areas. The multivariate analysis shows that not having an institutional delivery increases the probability of developing chronic malnutrition by 1.42 times. The higher the mother’s educational level, the less likely the minor is to develop chronic malnutrition. The greater the number of children under 5 years of age, the greater the risk of developing chronic malnutrition (PR: 1.39 and 1.67). Conclusion: It cannot be concluded that there is an association between non-institutional childbirth and chronic malnutrition in children under 5 years of age from low and extremely low socioeconomic levels in Peru.